How long is now? The multiple timescales of language processing. (2016) - Honey, Christopher J.; Chen, Janice; Müsch, Kathrin; Hasson, Uri
Abstract: Christiansen & Chater (C&C) envision language function as a hierarchical chain of transformations, enabling rapid, continuous processing of input. Their notion of a "Now-or-Never" bottleneck may be elaborated by recognizing that timescales become longer at successive levels of the sensory processing hierarchy – that is, the window of "Now" expands. We propose that a hierarchical "process memory" is intrinsic to language processing.